Phytochemical investigation and antimicrobial activity of Psidium guajava L. leaves - Metwally, A. M. (Medknow Publications, 2010)
Psidium guajava L. leaves were subjected to extraction, fractionation and isolation of the flavonoidal compounds. Five flavonoidal compounds were isolated which are quercetin, quercetin-3-O-α-L-arabinofuranoside, quercetin-3-O-β-D-arabinopyranoside, quercetin-3-O-β-D-glucoside and quercetin-3-O-β-D-galactoside. Quercetin-3-O-β-D-arabinopyranoside was isolated for the first time from the leaves. Fractions together with the isolates were tested for their antimicrobial activity. The antimicrobial studies showed good activities for the extracts and the isolated compounds.